Analisis Pengaruh Kualitas Layanan Elektronik Terhadap Kepuasan Pelanggan Pada Aplikasi Shopee - Nurhapirah Tasnim; Muhammad Irwan Padli Nasution (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The web could be utilized for of internet exchanging which is the reason frequently alluded to as web based business (electronic trade). The undeniably good web based business development in Indonesia has brought about a change in individuals' shopping designs towards on the web or internet shopping, consequently causing advertisers to learn different procedures so customers keep on feeling fulfillment while shopping utilizing applications, particularly.